Red dawn - Feitshans, Buzz; Beckerman, Barry 1942-1996; Milius, John 1944-; Swayze, Patrick 1952-2009; Howell, C. Thomas 1966-; Thompson, Lea 1961- (Twentieth Century Fox Home Entertainment, 1984)
When Communist paratroopers descend on a high school football field in Colorado, a group of the school's students wages an all-out guerrilla war to save their town and their country